Case Workers' Perspectives of Their Impact on First-Time, Female Status Offenders - Miller, Nikki Amanda (2019)
Female status offenders recidivate in the juvenile justice system within 1 to 3 years once released of the initial incarceration. The purpose of this basic qualitative study was to explore juvenile delinquent case workers' impact on first-time, female status offenders. Urie Bronfenbrenner's social ecological model informed the conceptual framework. The research instrument used for this study was the interview. Criteria for selecting 12 juvenile professionals to participate in the study included working 3 years or longer inside a women's forensic population, working with first-time offenders, having caseloads of female offenders, and focusing on the crime of status offenses. Initial and focused coding performed manually. Four major themes emerged from the data: trust, nurture, life-skills/life-tools, and parenting skills. An additional theme of anger emerged. The findings revealed the individual may exhibit positive social change by the implementations of practices involving life-skills/life-tools and parenting skills. One major recommendation included researching the model(s) an effectiveness of parenting skills program delivered to parents of first-time, female status offenders. Implications for social change included implementation of life-skills/life-tools and parenting skills to help minimize recidivism. Results of the study may stimulate new ideas for scholar-practitioners to examine and supply professionals within the forensic population with treatment strategies